Mitomycin alkaloids: synthetic studies - Gubler, Daniel Alan, author; Williams, Robert M., advisor; Rovis, Tomislav, committee member; Kennan, Alan J., committee member; Elliott, C. Michael, committee member; Luger, Karolin, committee member (Colorado State University. Libraries, 2009)
Documented herein are efforts towards the first asymmetric total synthesis of the mitomycin family of natural products. Methods have been developed that efficiently construct eight-membered ring precursors of the natural products. Additionally, a tetracyclic mitosane compound containing all the core features of the mitomycins except the C9a methyl aminal has been constructed. The above-mentioned synthetic efforts help set the stage for future completion of the asymmetric total synthesis of this family of compounds. The studies mentioned herein, while not totally successful, shed new light on the reactivity of the mitomycins as well as the remarkable electronic effect of the electron-rich arene ring.
Keywords: Mitomycin -- Synthesis; Alkaloids -- Synthesis